2019
DOI: 10.1038/s41467-018-08140-7
|View full text |Cite
|
Sign up to set email alerts
|

Chi3l3 induces oligodendrogenesis in an experimental model of autoimmune neuroinflammation

Abstract: In demyelinating diseases including multiple sclerosis (MS), neural stem cells (NSCs) can replace damaged oligodendrocytes if the local microenvironment supports the required differentiation process. Although chitinase-like proteins (CLPs) form part of this microenvironment, their function in this differentiation process is unknown. Here, we demonstrate that murine Chitinase 3-like-3 (Chi3l3/Ym1), human Chi3L1 and Chit1 induce oligodendrogenesis. In mice, Chi3l3 is highly expressed in the subventricular zone, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 65 publications
1
52
1
Order By: Relevance
“…41 Although CHIT1 function in the CNS is not yet clear, a recent study shows that, like murine CHI3L3, human CHI3L1 and CHIT1 induce oligodendrogenesis in vitro. 42 First single-cell sequencing data emerged from a cancer context, where a branch of intratumoral macrophages was composed of 3 clusters with as top upregulated genes TREM2, APOE, CD68, and CHIT1. Despite this coregulation as part of the same branch, these genes were differentially expressed among the 3 clusters, with CHIT1 correlating the most with increasing intratumoral macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…41 Although CHIT1 function in the CNS is not yet clear, a recent study shows that, like murine CHI3L3, human CHI3L1 and CHIT1 induce oligodendrogenesis in vitro. 42 First single-cell sequencing data emerged from a cancer context, where a branch of intratumoral macrophages was composed of 3 clusters with as top upregulated genes TREM2, APOE, CD68, and CHIT1. Despite this coregulation as part of the same branch, these genes were differentially expressed among the 3 clusters, with CHIT1 correlating the most with increasing intratumoral macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…67 It is conceivable that in our EAE model, increased expression of Ptk2b triggered by MSC therapy, led to improvement of the PERG amplitude via modulation of neuronal activity at the PSD95 terminals in the inner plexiform layer. Furthermore, expression of Ptk2b seems to be a critical upstream regulator in Chi3l3-induced oligodendrogenesis, 68 which could have a positive effect on optic nerve myelination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that Ym1/2 promoted interleukin-17 (IL-17)–mediated neutrophilia and was involved in nematode killing and host damage in mice ( 16 ). It was also suggested that Ym1 induced oligodendrogenesis, and silencing Ym1 increased the severity of EAE ( 17 ). Furthermore, Ym1/2 promoted T H 2 (T helper 2) cytokine expression implicated to regulate allergic inflammation by inhibiting 12/15( S )-lipoxygenase in mice ( 18 ).…”
Section: Introductionmentioning
confidence: 99%